PENGARUH MANIPULASI IKLIM KANDANG MELALUI PENGKABUTAN TERHADAP TOTAL ERITROSIT, LEUKOSIT, DAN HEMATOKRIT KAMBING PE DAN SAPERA - Heri Irawan; Erwanto Erwanto; Siswanto Siswanto; Arif Qisthon (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2021)
This study aimed to determine the effect of microclimate manipulation with fogging on the total erythrocyte, leukocyte, and hematocrit of Ettawa Grade (EG) and Sapera goats. The research was conducted from April to May 2020, at Telaga Rizki People's Farm, Metro City, Lampung Province. Blood tests were conducted at the Pramitra Laboratory in Bandar Lampung. The study used a split-plot experimental design with the basic design of a Completely Randomized Design (CRD). This study used 2 treatments and 3 replications. The main plots were the climate manipulation of fogging and without fogging of the pen, while the subplots were EG and Sapera goats. The research data were analyzed with the assumptions analysis of variant 5% and if significantly different then proceed with BNT test. The results showed that the cage climate manipulation treatment had no significant effect (P> 0.05) on total erythrocyte, total leukocyte, and hematocrit. Erythrocyte values at P0 (0,73 million/mm3) and P1 (0,89 million/mm3); leukocyte values at P0 (13,43 thousands/mm3) and P1 (14.74 thousands/mm3); and the hematocrit values at P0 (3,02%) and at P1 (3,92%). Keywords : Climate manipulation, Erythrocyte, hematocrit, leukocyte, PE goat, sapera goat